2007
DOI: 10.1227/01.neu.0000298898.38979.e3
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Insults in Subarachnoid Hemorrhage

Abstract: Elevated ICP not responding to treatment is predictive of clinical deterioration, whereas high CPP decreases the risk of clinical deterioration. It may be beneficial to not lower spontaneous high CPP in patients with subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…PTD ICP15 , PTD ICP20 , PTD ICP25 and PTD ICP30 ) as defined by different predefined ICP threshold (15,20,25 and 30 mmHg). Values are expressed as relative frequencies (%) for categorical variables and medians (ranges) for continuous factors.…”
Section: Supplemental Table II Univariate Logistic Regression Analysmentioning
confidence: 99%
See 2 more Smart Citations
“…PTD ICP15 , PTD ICP20 , PTD ICP25 and PTD ICP30 ) as defined by different predefined ICP threshold (15,20,25 and 30 mmHg). Values are expressed as relative frequencies (%) for categorical variables and medians (ranges) for continuous factors.…”
Section: Supplemental Table II Univariate Logistic Regression Analysmentioning
confidence: 99%
“…15 Univariate analysis demonstrated that HICP increased the risk of clinical deterioration without significant effect on functional outcome. The burden of HICP has recently been more precisely characterized in traumatic brain injury (TBI) using a method that accounts for the cumulative extent and duration of HICP episodes, namely the ICP pressure-time dose (PTD ICP ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All SAH patients were managed according to a standardized protocol based on intensive physiological monitoring and aggressive therapy of any derangement to avoid or minimize secondary brain injury (4). All unconscious patients and patients with clinical and radiological signs of intracranial hypertension received a ventriculostomy.…”
Section: Methodsmentioning
confidence: 99%
“…Positron emission tomography (PET) studies have shown that subarachnoid hemorrhage (SAH) causes both global and focal hemodynamic and metabolic disturbances in the brain early after aneurysm rupture (1), which makes the brain vulnerability for secondary insults (24). Secondary ischemic brain injury may be caused by cerebral vasospasm and also by various other secondary insults, e.g., high intracranial pressure (ICP), hypotension, hypoxemia, and seizures.…”
Section: Introductionmentioning
confidence: 99%